Quality Visitor Experience On Post Pandemic Event: Evidence From The Event Of Jakarta Biennale 2021 - Gunadi, I Made Adhi; Erfinda, Yosi (Institut Pariwisata Trisakti, 2023)
The Covid-19 pandemic that hit the world at the beginning of 2020 has dealt a heavy impact on tourism activities globally, including the limitation of tourism events such as festivals or exhibitions. An adaptation step in organizing events by implementing added health and CHSE protocols create different visitor experience. This research then aims to examine the quality of the visitor experience at the Jakarta Biennale 2021 event as the first major art exhibition event to be held offline with the CHSE protocol. The quality of the visitor experience is reviewed in 7 qualitative descriptive dimensions of memorable tourism experiences, then the analysis is carried out using gap analysis. The findings show that the implementation of the CHSE protocol resulted in gaps in two dimensions of visitor experience (which are involvement and refreshment), but in general, does not reduce the quality of the visitor experience at the Jakarta Biennale event. As an implication, the implementation of the CHSE protocol can be continued and applied in the organizing of other events with some improvement. Keywords: Quality Visitor Experience, Tourism Experience, CHSE Protocol, Event Organizing, Post-Pandemic Event